USE OF MEAT-BONE PASTE AS A PROTEIN SOURCE IN MEAT PRODUCT PRODUCTION - A. K. Kakimov; B. B. Kabulov; Zh. S. Yessimbekov; N. A. Kuderinova (Теория и практика переработки мяса, 2016)
In this paper, the results of the experimental research on developing the technology of a protein complex based on the meat-bone paste and protein-fat-blood emulsion are shown. The technological scheme of meat-bone paste production on the basis of complex grinding meat-bone raw material to bone particle size of 100 ∙10–6 m and further processing of bone particles using reagent, cheese whey, with pH 4,3 is presented. When studying the nutritive and biological value of the protein complex, it was established that the protein complex consisting of the food component from bone and protein-fat-blood emulsion could be used instead of the basic raw material in meat product production. The comparative analysis of the nutritive value of the protein complex and horse meat demonstrated the following results: the amino acid composition of the protein complex showed a balance of the essential amino acids and the high content of the essential amino acids which limit the biological value: lysine, leucine and threonine. The high content of polyunsaturated fatty acids was observed, which justified the biological value of the protein complex.